2011
DOI: 10.4049/jimmunol.1003050
|View full text |Cite
|
Sign up to set email alerts
|

CD5 Promotes IL-10 Production in Chronic Lymphocytic Leukemia B Cells through STAT3 and NFAT2 Activation

Abstract: B lymphocytes from chronic lymphocytic leukemia (CLL) display some CD5 transcripts for CD5 containing the known exon 1 (E1A) and other CD5 transcripts containing the new exon 1 (E1B). These malignant B cells, as well as B cell lines transfected with cDNA for E1A-cd5 or with cDNA for E1B-cd5 produce IL-10, raising the possibility that CD5 participates in the secretion of IL-10. We identified transcription factors involved in this production in CD5+ B lymphocytes from CLL patients and in E1A-cd5–transfected or E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 50 publications
6
60
0
1
Order By: Relevance
“…Similar pattern of survival and apoptosis responses following anti-CD5 stimulation were obtained in the study of PerezChacon and collaborators (Perez-Chacon et al, 2007). Moreover, authors showed that in unstimulated and resting CD5 transfected B cells, it was observed that CD5 + B cells produce more IL-10 than CD5 -B cells enhancing survival of B cells , Garaud et al, 2011.…”
Section: Calcium Signaling and Chronic Lymphocytic Leukemia 383supporting
confidence: 63%
“…Similar pattern of survival and apoptosis responses following anti-CD5 stimulation were obtained in the study of PerezChacon and collaborators (Perez-Chacon et al, 2007). Moreover, authors showed that in unstimulated and resting CD5 transfected B cells, it was observed that CD5 + B cells produce more IL-10 than CD5 -B cells enhancing survival of B cells , Garaud et al, 2011.…”
Section: Calcium Signaling and Chronic Lymphocytic Leukemia 383supporting
confidence: 63%
“…We propose that the CD5 marker is an acceptable measure of Breg cells based on our data demonstrating a high correlation with CD24 hi CD38 hi and IgM + CD5 + subpopulations. CD5 is reported to induce IL-10 expression and promote cell survival in human B cells (27), human chronic lymphocytic leukemia B cells (28), and mice (29). In mice, CD5 + CD1d + B cells secrete IL-10 and have a regulatory function evidenced by their inhibition of INF-g and TNF-a expression in T cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…CD5-positive CLL B cells also proliferate in response to CpG, however, to a lesser extent (Figure 3 3.3. CpG stimulation leads to IL-10 production CLL B cells are known to secrete high amounts of the anti-inflammatory cytokine IL-10, mainly due to their elevated CD5 expression [17]. To test whether there is a difference between the CD5-negative and CD5-positive B cells of the patients regarding this ability, IL-10 production was measured from cell culture supernatants after stimulation with anti-BCR, CpG and their combination.…”
Section: Proliferation Of Cll B Cellsmentioning
confidence: 99%